KEHIDUPAN PETANI DI RAWANG JAYA NAGARI KAMBANG UTARA KECAMATAN LANGAYANG KABUPATEN PESISIR SELATAN STUDI KASUS: DARI PETANI TALAS MENJADI PETANI KELAPA SAWIT (1997-2012) - Fitri, Fitri; Hardi, Etmi; Aziz, Zulkifli (Pendidikan Sejarah, 2014)
The farmerâs life in Rawang Jaya Nagari Kambang Utara, Kecamatan Lengayang, Kabupaten Pesisir Selatan. History Education Program. STKIP PGRI West Sumatra. Padang 2014. This thesis discusses about the change of life taro farmer be oilpalm farmer. The study very interesting for research because it can see the process of change live hood and impact for socio-economic life Rawang Jayaâs society in Nagari Kambang Utara. To facilitate this research, the problem can be formulated as follows: (1) why does Rawang Jayaâs society move to be oilpalm farmer. (2) How does the socio-economic life of people In Rawang Jaya in Nagari Kambang Utara after be an oil palm farmer in 1997-2012? The purposes of this research are (1) to explain why people in Rawang Jaya move to be oil palm farmer. (2). To Describe the socio-economic life people in Rawang Jaya in Nagari Kambang Utara after be a oil palm farmer 1997-2012). This research use historical method. The method consists of the following four stages namely Heuristic, Doing Criticism Sources, Interpretation, Historiography. (1) Heuristic is a collect the data, looking for the source and concludes to library study and interviews. (2) Criticism source, in order to obtain the facts of history. (3) Interpretation, the obtained data analyzed and interpreted with connecting and comparing the observed facts so the fact that ready to be served. (4) Historiography, writing in the form of scientific papers after collect the data and facts that really accurate and valid then write in the form of a thesis. This study describes the results: ( 1 ) the reason of why the society move from be the taro farmer to oil palm farmer in Rawang Jaya Kambang Utara , because there are several factor, the condition of soil make the society to planting taro cops, the cheaper of taro also make the society should hard working to get more income, and the willingness of the society to life better. (2) The socio-economic life People in Rawang Jaya in Nagari Kambang Utara after being a oil palm farmer in 1997-2012 have change, the education of that society also growing and give good impact for society life style .